Pengaruh Bullying Yang Mengakibatkan Tindak Pidana oleh Anak di Bawah Umur di Indonesia (Studi Kasus Ditinjau Berdasarkan Undang-Undang Nomor 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak) - Sitinjak, Anggi Dwita Clara Afrilia; Astuti, Retno Dwi; Novia, Elsa Ari; Kristoffel, Chesario Own; Rahmandika, Surya Afif; Febrianty, Yenny (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Bullying is the act of attacking someone who is considered to have power or power to parties weaker than him. This act of bullying can be in the form of verbal assault or physical assault, and can be in the form of sexual harassment. This study aims to provide knowledge that bullying can be the cause of a minor perpetrator becoming a child offender. This normative analytical descriptive juridical research describes the examination of legal certainty about criminal acts by minors. Children's ability to think maturely is still limited, so they remain vulnerable to the potential to be subjects both as victims and perpetrators of criminal acts. Restorative justice is an alternative to solving problems such as bullying in the juvenile justice system to provide opportunities for children through coaching.